2019
DOI: 10.29252/jhehp.5.2.7
|View full text |Cite
|
Sign up to set email alerts
|

The Antibacterial and Antioxidant Effects of Clove (Syzygium aromaticum) and Lemon Verbena (Aloysia citriodora) Essential Oils

Abstract: Considering the consumer demand for natural food preservatives, researchers have been attempting to identify alternative natural and safe sources of edible antioxidants and antimicrobials [2]. Various antimicrobial compounds are found in nature, which are mostly involved in providing defense against numerous microorganisms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 24 publications
(33 reference statements)
1
18
0
Order By: Relevance
“…2). Hosseini et al (2019), reported similar observations. They have observed inhibition zones of approximately 12.05 mm for E. coli PTCC 1399 and slightly larger zones for the Gram-positive Bacillus cereus PTCC 1154 (13.25 mm).…”
Section: Resultssupporting
confidence: 64%
“…2). Hosseini et al (2019), reported similar observations. They have observed inhibition zones of approximately 12.05 mm for E. coli PTCC 1399 and slightly larger zones for the Gram-positive Bacillus cereus PTCC 1154 (13.25 mm).…”
Section: Resultssupporting
confidence: 64%
“…The improvement of the serum oxidative status in the rats administered with 200 mg/kg of the extract was considered more significant compared to the metformin group. The antioxidant potential of the nutmeg extract in the diabetic groups could be attributed to the natural phenolic substances of this plant as previously described [20][21][22][23][24][25].…”
Section: Effects Of the Extract On The Serum Mda And Tacmentioning
confidence: 66%
“…The radical scavenging activity of the nutmeg extract in the current research could be allotted to the presence of polyphenols and flavonoids. In plants, phenolic compounds are mainly produced by the secondary metabolism, and the antioxidant properties of phenolic compounds largely depends on their redox properties, which enable their action as reductive agents, hydrogen donors, and singlet oxygen quenchers [22]. Some of the natural antioxidants belonging to the flavonoid compounds (flavonols, flavones, isoflavones, and pterocarpans) have been isolated from the M. fragrans seed [7].…”
Section: Antioxidant Capacity Based On Dpph Testmentioning
confidence: 99%
“…An investigation conducted by Hosseini et al found that AC EO has potent antioxidant activity compared with the positive control (BHT), with IC 50 values of 11.33 ± 01 and 27.43 ± 04 μg/mL, respectively [ 30 ]. The presence of heteroatom-containing compounds in the EOs can induce antioxidant activity, Oxygen containing moieties like phenols or hydroxyl have antioxidant activity more potent than Nitrogen-containing structures like aniline [ 31 ], However, Citral is the main component of various plants was reported as antioxidant agents [ 32 ] and in our EOs of AC one of the main component was the α-Citral from both regions, as well as more chemical components with Oxygen atom-like Methyl lineoleate and [2,2-Dimethyl-4-(3-methyl but-2-enyl)-6-methylidenecyclohexyl] methanol was observed in the EOs of AC from Baqa al-Gharbiyye in quantities two-three times more than Umm al-Fahm EOs, and this can explain the antioxidant activity of both EOs and the more potent activities regarding Baqa al-Gharbiyye than Umm al-Fahm EOs.…”
Section: Discussionmentioning
confidence: 99%
“…Oukerrou et al found that AC EO inhibited the growth of E. coli and S. aureus, with MIC values of 8.37 and 5.84 mg/mL, respectively [27]. Another study conducted by Hosseini et al evaluated the antibacterial activity of AC EO using the microdilution method and found that it has antibacterial activity against E. coli, P. aeruginosa, and S. aureus, with MICs of 2500, 2500, and 1250 μg/mL, respectively [30]. Among the EO compounds, the aromatic containing compounds like carvacrol, thymol, eugenol, and cinnamaldehyde appear to have interesting antimicrobial activities as well as the aliphatic components, like nerol, linalool, citral, geraniol, perillaldehyde, and α-terpineol, possess potent antimicrobial activities [33], the antibacterial mechanism of these aromatic and aliphatic compounds is that in their lipophilic ability to partition in the lipophilic lipids of the mitochondria and cytoplasmic membrane as well as they could disturb the structures, and resulting in leakage of bacterial cell contents [34].…”
Section: Antimicrobial Effectmentioning
confidence: 99%